Peran Analisis Kebijakan Pendidikan dalam Mewujudkan Sistem Pendidikan yang Berkualitas - Agung Marta Pratama; Osna Yenti; Ken Hawari; M. Ali Basroh; Anggia Pratiwi (STKIP Subang, 2026)
Educational policy analysis plays a strategic role in realizing a high-quality and sustainable education system. Educational policy functions not only as a guideline for the implementation of education but also as an important instrument in improving the quality of learning processes, ensuring students’ holistic development, fostering exemplary behavior and moral values, and addressing challenges in policy implementation. This study aims to examine the role of educational policy analysis in achieving a quality education system. The research employs a library research method by reviewing relevant literature such as books, scholarly journals, articles, and official documents. The findings indicate that educational policy analysis contributes to improving learning quality through rational and contextual policies, ensuring comprehensive student development, strengthening moral values and role modeling in education, and identifying as well as overcoming challenges in educational policy implementation. Therefore, educational policy analysis is a key element in supporting the realization of a quality, equitable, and responsive education system in facing contemporary challenges.